Postmodern Aspects of Electronic and Multimedia Music - Septian Dwi Cahyo (Jurnal Kajian Seni, 2020)
Modernism spirit in the music of doing something new, create innovation and so on now facing an obstacle because material progression in new music become smaller and smaller. Based on this phenomenon, now composers nd other ways to develop their musical landscapes such as breaking the boundaries between music and other arts form until involving Postmodern aesthetic tendencies in their works. Many composers now breaking the boundaries of Modernism myth such as breaking binary opposition between high and pop culture, past and present and make it as another strategy to make music and also to give an alternative solution to the “hibernation” of material progression in new music. These phenomena are clearly appear in electronic and multimedia music where composers using many existing audio quotations from pop culture, using pop art element, and also using an existing audio quotation as a parody.